1991
DOI: 10.1128/jcm.29.2.277-282.1991
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of phenotypic tests for identification of Acinetobacter species

Abstract: hydrolysis, and assimilation of 14 carbon sources. Of the strains tested, 181 represented 12 DNA groups in the matrix; at a probability level of .0.95, 78% of them were correctly identified, 2.2% were misidentified, and 19.8% were not identified. Seventeen strains represented two DNA groups not included in the matrix; nine of them were incorrectly assigned to a DNA group by these phenotypic tests. Because of problems of separating strains belonging to DNA groups 1, 2, 3, and 13 by using the phenotypic tests pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
143
0
7

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(155 citation statements)
references
References 18 publications
(23 reference statements)
5
143
0
7
Order By: Relevance
“…Willcox probability scores (Willcox et al 1973) were calculated and an identification accepted if ¼ 0AE99. A modal likelihood score, as the modal likelihood fraction (Dybowski and Franklin 1968) was calculated by pibwin as a measure of the goodnessof-fit for a most likely identification (Gerner-Smidt et al 1991;Bryant 2000); a satisfactory match was indicated when the modal likelihood score was ¼ 0AE01.…”
Section: Probabilistic Identificationmentioning
confidence: 99%
“…Willcox probability scores (Willcox et al 1973) were calculated and an identification accepted if ¼ 0AE99. A modal likelihood score, as the modal likelihood fraction (Dybowski and Franklin 1968) was calculated by pibwin as a measure of the goodnessof-fit for a most likely identification (Gerner-Smidt et al 1991;Bryant 2000); a satisfactory match was indicated when the modal likelihood score was ¼ 0AE01.…”
Section: Probabilistic Identificationmentioning
confidence: 99%
“…Due to the high level of genotypic and phenotypic similarity among Acinetobacter calcoaceticus, A. baumannii, Acinetobacter genomic species 13TU and Acinetobacter genomic species 3, they are grouped together as the A. calcoaceticus-A. baumannii (Ac-Ab) complex [25].…”
Section: Discussionmentioning
confidence: 99%
“…Many species in the Acinetobacter genus, such as Acinetobacter genomospecies 3 and Acinetobacter genomospecies 13, are more recently recognized as important but distinct nosocomial pathogens (Higgins et al 2007). However, detection of these particular organisms is complicated because they are closely related genetically (gyrB) and difficult to differentiate phenotypically (Gerner-Smidt et al 1991;Gerner-Smidt 1992;Yamamoto et al 1998;Higgins et al 2007). Therefore, these unnamed species tend to be grouped with Acinetobacter calcoaceticus in the Ac.…”
Section: Discussionmentioning
confidence: 99%
“…baumannii specificity observed in this assay may or may not prove useful for clinical diagnostics, as treatment may be the same regardless of the Acinetobacter infection. Some researchers have questioned whether there is a need for species identification amongst the Acinetobacter genus (Gerner-Smidt et al 1991). Others argue that it is necessary to distinguish between the Ac.…”
Section: Discussionmentioning
confidence: 99%